Long-term changes in the tree radial growth and intrinsic water-use efficiency of Chuanxi spruce (Picea likiangensis var. balfouriana) in southwestern China - Wang, Yang; Zhang, Yong; Fang, Ouya; Shao, Xuemei (Journal of geographical sciences, 2018)
Elevated CO 2 level in the atmosphere is expected to improve the tree growth rates and intrinsic water-use efficiency (iWUE). Although current results inferring from tree rings found the tree growth decline in water-limited area, it is still unclear whether spruce trees in humid southwestern China benefit from the increasing CO 2 . In this study, tree-ring width data were used to investigate the tree radial growth rate of Chuanxi spruce (Picea likiangensis var. balfouriana). Moreover, combining with the tree-ring carbon isotope date, we analyzed the physiological responses of Chuanxi spruce to rising CO 2 concentrations in the atmosphere (Ca) associated with climatic change in southwestern China. From 1851 to 2009, iWUE of Chuanxi spruce rose by approximately 30.4%, and the ratio of atmospheric CO 2 to leaf intercellular CO 2 concentration (Ci/Ca) showed no significant trend in the study area. The result suggested that Chuanxi spruce used an active response strategy when Ca was significantly increased. iWUE showed a significant increasing trend in parallel with tree radial growth, indicating that the increasing iWUE resulted in an increase in radial growth. These results suggest that spruce forests in southwestern China have not shown declining trends under increasing Ca and climate change scenarios, in contrast to trees growing in water-limited areas. Therefore, spruce forests benefit from the increasing CO 2 in the atmosphere in the humid areas of southwestern China.